Isotope analysis of the nutrient supply in Xiangxi Bay of the Three Gorges Reservoir - Yang, Liu; Liu, Defu; Huang, Yuling; Yang, Zhengjian; Ji, Daobin; Song, Linxu (Ecological engineering, 2015)
Nutrients are material basis of eutrophication and algal blooms in the water body. Xiangxi Bay (XXB), the largest tributary bay in the lower reach of the Three Gorges Reservoir (TGR), is subject to such eutrophication and algal blooms. In order to investigate the supply patterns of nutrients in XXB, stable isotopes of hydrogen (δD) and oxygen (δ18O), nutrients, and flow velocity were observed from September 2012 to December 2013. A two-compartment linear mixing model based on the tracer principle of δD and δ18O was employed to calculate the water and nutrients contributions to XXB from the mainstream of TGR and the upper tributaries of the XXB. The average nutrients concentrations of XXB were estimated and compared to the observed values in the field. The results suggested that there was obvious layered and bidirectional density current in XXB, which had a significant impact on nutrient supply pattern and spatial and temporal distribution of the isotopes and nutrients in XXB. The water contributions of the mainstream of TGR and the upper tributaries for XXB were 84% and 16%, respectively. Moreover, the nitrogen and phosphorus nutrients imported into XXB through the mainstream of TGR were over 80% and 60%, respectively, higher than those of the upper tributaries. The calibration of nutrients concentration in XXB showed that the error between the calculated and the observed was about within 20%, which confirmed further the reliability that the nutrients in XXB come mainly from the mainstream of TGR. The results address the attention that the pollution control should be implemented not only in the tributary watershed, but also the whole upstream region of the TGR for prevention of its tributaries algal blooms.